Semecarpus pulvinatus - Hoo, P.K.; Tsen, S.; Damit, A.; Khoo, E.; Colin Ruzelion Maycock; Nilus, R.; Sugau, J.; Tanggaraju, S.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2020)
Semecarpus pulvinatus is restricted to the Deramakot and Sungai Tiagau (Extension) Forest Reserves in Sabah, Malaysia. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are both 8 km 2. The species is protected in situ in Sungai Tiagau (Extension) Forest Reserve. It is inferred that there is a continuing decline of habitat of this species as Deramakot is a commercial forest. Hence, it is assessed as Endangered. Semecarpus pulvinatus is endemic to Sabah, Malaysia. It is restricted to the Deramakot and Sungai Tiagau (Extension) Forest Reserves.